Neuroinflammation and Peripheral Immune Infiltration in Parkinson's Disease: An Autoimmune Hypothesis - Angela J. Monahan; Michael Warren; Paul M. Carvey (Cell Transplantation, 2008)
Despite decades of research and the development of a large group of animal models, our understanding of the mechanisms responsible for the progressive loss of dopamine neurons in Parkinson's disease (PD) is unknown. So-called neuroprotective studies demonstrate that a vast group of molecules readily attenuate the dopamine (DA) neuron loss produced by DA neurotoxin insult. Despite these successes, these neuroprotective strategies have been surprisingly ineffective in patients. This may reflect the fact that the initial pathogenic event and the subsequent disease progression is a consequence of different mechanisms. As we began to think about this disconnect, we discovered that animals exposed to DA neurotoxins exhibited blood–brain barrier (BBB) dysfunction. If the BBB in PD patients is disrupted, then the barrier that normally segregates peripheral vascular factors from brain parenchyma is no longer present. Immune cells could then enter brain and produce a self-perpetuating (progressive) degenerative process. In this review, we propose that peripheral immunity contributes to the degenerative process of PD and may be responsible for the progressive nature of the disease. This hypothesis is supported by a broad and diverse literature that is just beginning to come together to suggest that PD is, in part, an autoimmune disease. In order to understand this hypothesis, the reader must question the conventional wisdom that the BBB is intact in PD, the brain is an immune privileged area, and that pathogenic insult and disease progression may reflect different mechanisms.